2002
DOI: 10.1080/09687680110112929
|View full text |Cite
|
Sign up to set email alerts
|

Multiple levels of Notch signal regulation (Review)

Abstract: Notch is a vitally important signalling receptor controlling cell fate determination and pattern formation in numerous ways during development of both invertebrate and vertebrate species. An intriguing pathway for the Notch signal has emerged where, after ligand-dependent proteolysis, an intracellular fragment of the receptor itself translocates to the nucleus to regulate gene expression. The nuclear activity of the Notch intracellular domain is linked to complexes regulating chromatin organization through his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 134 publications
0
62
0
3
Order By: Relevance
“…The Kuzbanian gene, which belongs to the a-disintegrin and metalloproteinase superfamily of metallopro-teinases, is one of several protease genes that play critical roles in both Notch receptor and ligand maturation, regulation and function. [34][35][36][37] These data suggest that AC133+CD34À cells have distinct Notch receptor expression, which may relate to differential responsiveness to the Notch ligands.…”
Section: Phenotypic Isolation Of Human Cb Cd34à and Cd34+ Cell Subsetsmentioning
confidence: 82%
See 1 more Smart Citation
“…The Kuzbanian gene, which belongs to the a-disintegrin and metalloproteinase superfamily of metallopro-teinases, is one of several protease genes that play critical roles in both Notch receptor and ligand maturation, regulation and function. [34][35][36][37] These data suggest that AC133+CD34À cells have distinct Notch receptor expression, which may relate to differential responsiveness to the Notch ligands.…”
Section: Phenotypic Isolation Of Human Cb Cd34à and Cd34+ Cell Subsetsmentioning
confidence: 82%
“…One line of evidence to support this as a potential mechanism comes form Uyttendale's group, which using an endothelial cell line has shown that Jagged-1 may act via Notch-4. 44 However, because of the presence of multiple Notch receptors and ligands, and a whole array of modulators that appear to act in context-specific manner, 37,45 there are other potential expalanation for the lack of reponse of CD34À cells to Jagged-1. For instance, Jagged-1-induced activation through Notch-1 and Notch-2 has been shown to be negatively regulated by the expression of Fringe in the receiving cell.…”
Section: Discussionmentioning
confidence: 99%
“…Many receptors have been found to be cleaved and imported into the nucleus, including Notch, epidermal growth factor receptor and a C-terminal fragment of a voltage-gated Ca 2+ channel [41][42][43], suggesting that this is a cellular strategy often used to establish communication between the plasma membrane and the nucleus. A common feature is that receptor fragments, often in combination with transcription factors, regulate transcription.…”
Section: Frizzled Finds Its Way To the Nucleusmentioning
confidence: 99%
“…The extracellular domain (ECD) is comprised of between 29 and 36 epidermal growth factor (EGF)-like repeats and three copies of a lin-12/Notch Glp motif. The intracellular domain (ICD) has a RAM23 region, seven CDC10/Ankyrin repeats and a PEST (proline, glutamate, serine, threonine-rich) region (Jeffries and Capobianco, 2000;Baron et al, 2002). Notch4/Int3 (ICD4) is smaller than Notch1ICD and lacks the transcriptional activation domain (TAD) and cytokine response (NCR) sequence found in the Notch1ICD (Uyttendaele et al, 1996;Allenspach et al, 2002).…”
Section: Introductionmentioning
confidence: 99%